PERBANDINGAN KADAR HEMOGLOBIN ANTARA METODE SPECTROPHOTOMETER DENGAN METODE HEMOCUE PADA SAMPEL LEUKOSITOSIS - Basti Andriyoko; Leni Lismayanti; Delita Prihatni (INDONESIAN JOURNAL OF CLINICAL PATHOLOGY AND MEDICAL LABORATORY, 2009)
Background and objective: The measurement of haemoglobin was carried out by using hematology analyzer with specthrophotometermethod which measured light absorbance at 540 nm. However, this measurement affected by increase turbidity as a result of leucocytosis.The turbidity can be eliminated by using HemoCue method that detect absorbance at 570 nm and 880 nm. The aim of this study wasto compare the measurement of haemoglobin obtained between specthrophotometer method and HemoCue method. Materials andmethod: Blood EDTA sample that have been measured with MEK-6318K Nihon Kohden hematology analyzer for haemoglobin levelswith spectrophotometer methods with leucocyte > 100.000/mm3 were included in this study. Blood sample are measured again forthe haemoglobin level with HemoCue B-Haemoglobin Analyzer. This study was conducted at Clinical Pathology Laboratory, Dr. HasanSadikin Hospital Bandung from August–October 2008. Result: Seventeen leucocytosis sample were enroled in this study. The meanhaemoglobin level from specthrophotometer method is higher than HemoCue method, however there was no statistically significantdifference between haemoglobin result from specthrophotometer method and HemoCue method (p = 0.742 > a = 0.05). Conclusion:There was no significant difference beetween specthrophotometer method and HemoCue method for haemoglobin measurement ofleucocytosis sample.